Hukum Zakat Profesi Perspektif Majlis Ulama Indonesia (MUI) - Mohamad Ma’mun (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2021)
Occupational zakat was not known at the Prophet Muhammad era until the next few hundred years. However, it should be noted that during the Prophet Muhammad era, there have been various occupations in which the income are different from the present. In ancient times, rich people usually come from trading, farming and raising livestock. On the other hand, those occupations nowadays are not usually made people becoming rich. Nowadays, several occupations have greater opportunities to bring wealth such as specialist doctors, architects and lawyers. But according to classical fiqh, these occupations are not obligated to pay zakat, even though they bring huge profits. On the contrary, the traders, farmers and ranchers who are now dominated by the poor have been obligated to pay zakat. Based on that case, contemporary Islamic thinkers suggest an idea to issue occupational zakat for the modern occupations. Meanwhile in Indonesia, the Indonesian Council of Religious Scholar (MUI) has officially issued a fatwa on the law of occupational zakat. Through its fatwa No. 3 in 2003, the Indonesian Council of Religious Scholar (MUI) stated that the occupational zakat is a mandatory.